2017
DOI: 10.1021/acs.iecr.6b03846
|View full text |Cite
|
Sign up to set email alerts
|

Noncatalyzed Liquefaction of Celluloses in Hydrothermal Conditions: Influence of Reactant Physicochemical Characteristics and Modeling Studies

Abstract: This paper reports a fundamental study on the hydrothermal liquefaction of cellulose into light products. First it aimed at comparing the noncatalyzed intrinsic reactivity of model celluloses such as Avicel and Sigmacell with various physicochemical characteristics (degree of polymerization, crystallinity, particle size, morphology). This information is of importance to dissociate the chemophysical phenomenon from the catalytic one in the case of catalytic liquefaction to better evaluate the added-value of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…Many literature studies have indicated that HTL conditions, like reaction temperature and holding time, were the inuential factors of the biocrude yield and the liquefaction conversion. [33][34][35] These condition parameters play a decisive role in the decomposing of microalgae and the formation of biocrude. Hence, the inuence on the reaction temperature and holding time was studied.…”
Section: Hydrothermal Catalytic Liquefaction Results With Different Omentioning
confidence: 99%
“…Many literature studies have indicated that HTL conditions, like reaction temperature and holding time, were the inuential factors of the biocrude yield and the liquefaction conversion. [33][34][35] These condition parameters play a decisive role in the decomposing of microalgae and the formation of biocrude. Hence, the inuence on the reaction temperature and holding time was studied.…”
Section: Hydrothermal Catalytic Liquefaction Results With Different Omentioning
confidence: 99%
“…Cellulose and hemi-cellulose originated compounds were present at smaller quantities compared to their lignin counterparts. Most noteworthy are the products from acid-catalyzed treatment (by hydronium ions H3O + ) of cellulose such as furfurals and organic acids [17]. All pre-specified compounds were present in the organic yields with only 10 compounds reporting concentrations below 0.01 wt.%.…”
Section: Liquefaction Reactor Systemmentioning
confidence: 99%
“…The benefits from catalytic processing could be accounted for by reactor or process design improvements to valorize the by-products, such as for in-situ heat generation or hydrogen production or for Combined Heat and Power (CHP) purposes [15]. Recently, studies have examined the isolation of other factors such as feedstock morphology to better understand the added-value of catalytic treatment [17]. It is worth to mention that experimental findings have reported that for non-catalytic processing, 330 °C and 210 bar present more favorable conditions for Biocrude yield [12].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the nature of the catalysts (Brønsted/Lewis acid) and the nature of the atmosphere, the main product can be lactic acid, HMF, hexanedione or propylene glycol . In addition, the non‐catalyzed hydrothermal liquefaction of cellulose has been studied, which allows the dissociation of the chemophysical phenomenon from the catalytic one. Proper catalyst design avoids the formation of undesired humins.…”
Section: Figurementioning
confidence: 99%
“…They can be complex, but usually they are based on pseudo‐first order or power law single rate equations or on a full set of mass balance equations . These models can be selected in case of lack of detailed data as often observed in raw biomass conversion . They can be also helpful to determine relations between catalytic structure and catalytic activity…”
Section: Figurementioning
confidence: 99%